Jews of medieval "Slovenia" until the expulsions of 1496-1515 - Jelinčič Boeta, Klemen (Zgodovinski časopis, 2009)
The following article is discussing the Jewish presence in Carinthia, Styria, Carniola, Gorizia, Triest and Venetian Istria. The text begins in the late Antiquity, discusses the question of Jewish villages in Carinthia, Styria and Carniola and continues on a variety of subjects concerning the Jewish life of the area until the expulsions of 1946-1515 in comparison with the other two culturally close subdivisions of the Ashkenazi cultural area, the Northern Italy and Austria proper. A special attention is given to the contemporary Jewish sources, such as Isserlein, and to the questions of culture and dailz life.
Keywords: Isserlein; Jewish villages; Jews; Judje; judovske vasi; Middle Ages; Middle-Ages; Slovenia; Slovenija; srednji vek